Two cadmium(II) fluorous coordination compounds tuned by different bipyridines. Issue 5 (26th April 2017) - Kong, Ya-Jie; Li, Peng; Han, Li-Juan; Fan, Lu-Tong; Li, Peng-Peng; Yin, Shuang
Abstract : Two cadmium(II) fluorous coordination compounds with different bipyridine ligands, i.e. 2, 2′‐bipyridine and 4, 4′‐bipyridine, adopt different coordination modes (Cd—O or Cd—N coordination bonds) to form one‐dimensional chains. The supramolecular structures are constructed by π–π stacking, O—H…O hydrogen bonds and strong C—H…F—C interactions. Abstract : Fluorine is the most electronegative element and can be used as an excellent hydrogen‐bond acceptor. Fluorous coordination compounds exhibit several advantageous properties, such as enhanced high thermal and oxidative stability, low polarity, weak intermolecular interactions and a small surface tension compared to hydrocarbons. C—H…F—C interactions, although weak, play a significant role in regulating the arrangement of the organic molecules in the crystalline state and stabilizing the secondary structure. Two cadmium(II) fluorous coordination compounds formed from 2, 2′‐bipyridine, 4, 4′‐bipyridine and pentafluorobenzoate ligands, namely catena ‐poly[[aqua(2, 2′‐bipyridine‐κ 2 N, N ′)(2, 3, 4, 5, 6‐pentafluorobenzoato‐κ O )cadmium(II)]‐μ‐2, 3, 4, 5, 6‐pentafluorobenzoato‐κ 2 O : O ′], [Cd(C7 F5 O2 )2 (C10 H8 N2 )(H2 O)] n, (1), and catena ‐poly[[diaquabis(2, 3, 4, 5, 6‐pentafluorobenzoato‐κ O )cadmium(II)]‐μ‐4, 4′‐bipyridine‐κ 2 N : N ′], [Cd(C7 F5 O2 )2 (C10 H8 N2 )(H2 O)2 ] n, (2), have been synthesized solvothermally and structurally characterized. Compound (1) shows a one‐dimensional chain structure composed of Cd—O coordination bonds and is stabilized by π–π stacking and O—H…O hydrogen‐bond interactions. Compound (2) displays a one‐dimensional linear chain structure formed by Cd—N coordination interactions involving the 4, 4′‐bipyridine ligand. Adjacent one‐dimensional chains are extended into two‐dimensional sheets by O—H…O hydrogen bonds between the coordinated water molecules and adjacent carboxylate groups. Moreover, the chains are further linked by C—H…F—C interactions to afford a three‐dimensional network. In both structures, hydrogen bonding involving the coordinated water molecules is a primary driving force in the formation of the supramolecular structures.